2013
DOI: 10.1039/c3tb00545c
|View full text |Cite
|
Sign up to set email alerts
|

Extremely high inhibition activity of photoluminescent carbon nanodots toward cancer cells

Abstract: Highly water-soluble, biocompatible, and photoluminescent carbon nanodots (C-dots) having an average diameter 3.4 AE 0.8 nm and a quantum yield 4.3% are obtained from used green tea through grinding, calcination and centrifugation. The as-prepared C-dots are stable in high-ionic-strength media (e.g. 500 mM NaCl) and under light irradiation, allowing images of MCF-10A, MCF-7 and MDA-MB-231 cells to be recorded. The C-dots are mostly localized in the cell membranes and cytoplasms, with evidence of excitation-wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
120
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(130 citation statements)
references
References 77 publications
(111 reference statements)
6
120
0
Order By: Relevance
“…9-12 Among them, solvothermal methods using cheap and eco-friendly biomass such as green tea, sweet potatoes, honey, bamboo leaves, pomelo peel as the carbon sources to produce CDs have induced great interests due to their green chemistry nature. [13][14][15][16][17] The approach is also more costeffective as compared to those applied for synthesizing other fluorescence nanoparticles, such as noble metal nanoparticles and semiconductor QDs. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 3 One of the most fascinating characteristics of CDs is their photoluminescent capability.…”
Section: Introductionmentioning
confidence: 98%
“…9-12 Among them, solvothermal methods using cheap and eco-friendly biomass such as green tea, sweet potatoes, honey, bamboo leaves, pomelo peel as the carbon sources to produce CDs have induced great interests due to their green chemistry nature. [13][14][15][16][17] The approach is also more costeffective as compared to those applied for synthesizing other fluorescence nanoparticles, such as noble metal nanoparticles and semiconductor QDs. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 3 One of the most fascinating characteristics of CDs is their photoluminescent capability.…”
Section: Introductionmentioning
confidence: 98%
“…Till date there are so many methods adopted for the synthesis of carbon quantum dots including arc discharge [1], electrochemical synthesis [2,3], combustion/thermal/hydrothermal/acidic oxidation [4][5][6][7], cage-opening of fullerene [8], supported synthesis [9][10][11], microwave/ultrasonic [12,13], laser ablation [14,15] and electrochemical oxidation methods [16,17] and so on. Carbon quantum dots gained greater acceptance because of their wide application for instance in bioimaging [18,19], nanomedicine [20,21], photocatalysis [22,23], electrocatalysis [24,25], biosensing [26,27], and chemical sensing [28,29]. It was also used as Hg 2+ , Cu 2+ , Fe 3+ , Pb 2+ and Ag + sensors [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 98%
“…In fact, very recently Pierrat et al claimed that the toxicity of C-dots is mainly determined by the synthesis protocol [30]. Also, it has been reported that some food-based C-dots show anticancer properties, which strongly relies on the starting material employed for the synthesis [3132]. Keeping the aforementioned fascinating medicinal activities of selected spices in mind, highly fluorescent C-dots have been synthesized by a green one-pot hydrothermal route, using cinnamon, red chilli, turmeric and black pepper as starting materials.…”
Section: Introductionmentioning
confidence: 99%